Quantifying Uncertainty in Tortuosity Estimates for Porous Electrodes. Issue 7 (20th July 2021) - Mayilvahanan, Karthik S.; Hui, Zeyu; Hu, Kedi; Kuang, Jason; McCarthy, Alison H.; Bernard, John; Wang, Lei; Takeuchi, Kenneth J.; Marschilok, Amy C.; Takeuchi, Esther S.; West, Alan C.
Abstract : Measuring tortuosity in porous electrodes is important for understanding rate capability and optimizing design. Here, we describe an approach to determine electrode tortuosities and quantify the associated uncertainties by fitting a P2D model to discharge profiles from a standard rate capability test. A dimensionless current is identified as a design-of-experiment parameter that can be used to identify experiments that return confident estimates of tortuosity, even when other model parameters are not known with certainty. This approach is applied to analysis of L i x V 3 O 8 (LVO) electrodes and L i x N i 0.33 M n 0.33 C o 0.33 O 2 (NMC) electrodes. The details of the assumptions made in these measurements and their impact on the reported uncertainties are discussed. We also perform an uncertainty analysis on the standard method for quantifying tortuosity in the literature: electrochemical impedance spectroscopy collected under blocking electrolyte conditions. We find that confident estimates can be obtained using this approach even when uncertainties in equivalent circuit model parameters are considered.